2017
DOI: 10.1038/ismej.2016.187
|View full text |Cite
|
Sign up to set email alerts
|

Chemolithotrophic processes in the bacterial communities on the surface of mineral-enriched biochars

Abstract: Biochar and mineral-enriched biochar (MEB) have been used as soil amendments to improve soil fertility, sequester carbon and mitigate greenhouse gas emissions. Such beneficial outcomes could be partially mediated by soil bacteria, however little is known about how they directly interact with biochar or MEB. We therefore analyzed the diversity and functions of bacterial communities on the surfaces of one biochar and two different MEBs after a 140-day incubation in soil. The results show that the biochar and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 91 publications
0
51
0
Order By: Relevance
“…The resulting sequences were used for the analysis of operational taxonomic units (OTUs), with a sequence similarity threshold of 97%. Then the Ribosomal Database Program classifier Bayesian algorithm was used to perform taxonomic analysis using representative sequences of OTUs (Ye et al 2017). To calculate alpha diversity, we calculated the Chao1 and Shannon indices (Ye et al 2017).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The resulting sequences were used for the analysis of operational taxonomic units (OTUs), with a sequence similarity threshold of 97%. Then the Ribosomal Database Program classifier Bayesian algorithm was used to perform taxonomic analysis using representative sequences of OTUs (Ye et al 2017). To calculate alpha diversity, we calculated the Chao1 and Shannon indices (Ye et al 2017).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…It shows some selected physicochemical properties of biochar produced under different pyrolysis temperature with different feedstock types are summarized in Table 2. The highly porous nature of biochar and its high surface area are favorable habitats for soil biota (Jaafar et al 2014(Jaafar et al , 2015Ye et al 2017). The specific area and the porosity of biochar strongly depend on the type of feedstock as well as the production temperature.…”
Section: Biochar As a Growth Promoter For Soil Biotamentioning
confidence: 99%
“…Moreover, Farrell et al (2013) reported that the application of biochar improved the soil labile C content and soil pH and altered soil microbial community structure. Nevertheless, the highly porous structure of biochar provides habitats for microorganisms to colonize, permitting their growth in the soil environment (Awad et al 2018;Lehmann et al 2011;Quilliam et al 2013;Ye et al 2017). However, neutral/negative impacts of biochar on soil biological properties have also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…The 16S rRNA gene sequence was analyzed by SILVA (SSU123) database using a confidence threshold of 70% (Cole et al, 2013;Quast et al, 2013). The subsampling was based on the minimum sample sequence with equal sequencing depth (16,175 sequences per followed by clustering) (Ye et al, 2017). Diversity metrics, that is, richness (observed species), Chao richness index, Shannon diversity index, and coverage and phylogenetic diversity were calculated based on OTU tables using mother (v.1.30.1).…”
Section: Bioinformatic Analysis Of the 16srrna Ampliconsmentioning
confidence: 99%